2008
DOI: 10.1682/jrrd.2007.02.0026
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic monitoring of forearm muscles using one-dimensional sonomyography system

Abstract: Abstract-We introduce a method, known as one-dimensional sonomyography (1-D SMG), that uses A-mode ultrasound signals to detect dynamic thickness changes in skeletal muscle during contraction. We custom-designed a 1-D SMG system to collect synchronized A-mode ultrasound, joint angle, and surface electromyography (EMG) signals of forearm muscles during wrist extension. We extracted the 1-D SMG signal from the ultrasound signal by automatically tracking the corresponding echoes, which we then used to calculate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 47 publications
2
63
0
Order By: Relevance
“…We studied the relationship between the thickness deformation SMG of the forearm extensor and wrist angle during wrist extensionflexion. We discovered qualitatively similar profiles between the SMG and the wrist angle, suggesting a high degree of correlation [7,[20][21][22]. Furthermore, we found that SMG profiles from amputees performing hypothetical wrist extension-flexion were similar to those from nondisabled subjects [20].…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…We studied the relationship between the thickness deformation SMG of the forearm extensor and wrist angle during wrist extensionflexion. We discovered qualitatively similar profiles between the SMG and the wrist angle, suggesting a high degree of correlation [7,[20][21][22]. Furthermore, we found that SMG profiles from amputees performing hypothetical wrist extension-flexion were similar to those from nondisabled subjects [20].…”
Section: Introductionsupporting
confidence: 62%
“…In previous studies, we have proposed that the thickness deformation SMG of extensor carpi radialis muscle was closely correlated with wrist extension-flexion [7,20,23]. This close relationship is the basis for SMGbased prosthetic control.…”
Section: Control Strategymentioning
confidence: 86%
See 3 more Smart Citations